Actualization of Religious Moderation Values in Multi-Ethnic Schools - Ginting, Nurman; Limbong, Isman Efendi (Institut Agama Islam Sunan Giri (INSURI) Ponorogo, 2025)
This study aims to examine how the values of religious moderation are actualized in daily life in multi-ethnic schools in Medan City. The city of Medan, as a multicultural city, presents challenges as well as opportunities in fostering a tolerant and inclusive attitude among students from diverse religious and ethnic backgrounds. A qualitative approach was used in this study with case study methods in several secondary schools that represented this diversity. Data collection techniques are carried out through observation, in-depth interviews with teachers, principals, and students, and analysis of curriculum and school program documents. Data analysis techniques are carried out with the following steps: Data reduction, data presentation, data verification, and a conclusion drawn. Then, the data is processed using the ATLAS.ti 9 application. The results of the study show that the actualization of the value of religious moderation is reflected through the integration of tolerance materials in religious learning and PPKn, strengthening the role of teachers as agents of moderation, and the implementation of interfaith and cultural activities that strengthen social harmony. However, this study also found a number of challenges, such as the lack of teacher training in religious moderation and the external influence of social media that contains intolerance content. Therefore, synergy between schools, the government, and the community is needed to support the sustainability of religious moderation practices in a more systematic and sustainable manner.